Strategi Pemasaran Pada Rumah Susun BP Batam - Zahra Aqilla Putri Chandra; Maya Ariyanti (Jurnal Ecodemica : Jurnal Ekonomi Manajemen dan Bisnis, 2021)
One of the government agencies that builds and manages flats is BP Batam. BP Batam has flats located in 5 industrial areas in Batam, namely Batu Ampar, Sekupang, Muka Kuning, Tanjung Uncang and Kabil. However, there are still many people who are not interested in living in BP Batam flats. Although the facilities provided are quite complete. The purpose of this study is to provide a marketing strategy for BP Batam in marketing their flats. The method used in this research is descriptive qualitative by using the Forum Group Discussion (FGD) in collecting data. The results of this study indicate that the IFAS Matrix is 2.48 and the EFAS Matrix is 2.76, so that the IE Matrix is in cell 5. Then the marketing strategy should be the SO (Strength-Opportunity) Strategy. The SO (Strength-Opportunity) strategy was chosen because the strength value (1.825) in the IFAS Matrix is greater than the weakness value (0.6625). In addition, the opportunity value (1.717948718) on the EFAS Matrix is also greater than the threat value (1.051282051). The SO (Strength-Opportunity) strategy consists of (1) increasing the offer of temporary housing contracts to industrial workers outside Batam, (2) construct development with evenly distributed facilities/infrastructure, and (3) construct developments that are located spread across Batam.Keywords: External Condition Factors, IE Matrix, Internal Condition Factors, Proposed Marketing Strategy, and TOWS Matrix